INDIKASI GEOGRAFIS: REZIM HKI YANG BERSIFAT SUI GENERIS - Sasongko, Wahyu (Jurnal Media Hukum, 2012)
The existence of the Geographical Indication (GI) was estabilished at the same time as the TRIPs Agreement in 1994. In the TRIPs Agreement, GI is Intellectual Property Rights (hereafter IPR) regime that is typical of sui generis due to its distinctive features. It is reflected in the elements that are in the definition of GI. Basically, GI has set the use of Geographical names to recognise an object. Previously, the IPR regime had also set them, namely: Indication of Source (IS) and Apellation of Origin (AO), that were set in the Paris Convention in 1883, Madrid Agreement in 1891, and the Lisbon Agreement in 1958. Instead, the geographical names are also used as brands. The paper is a theoretical study towards two problems. First, the elements that become the characteristics of GI so that it is typical of sui generis. Second, the similiarities and the differences amongst GI and IS, AO and other trademarks. The findings of the study reveal that GI is typical of sui generis, reflected in the elements that are in the GI definition as it has already been agreed upon in the TRIPs Agreement. There are similiarities amongst GI and AS, AO and other trademarks, namely they can use the geographical names as a label on objects. Meanwhile, the differences are in the elements themselves. IS has the simplest element, followed by GI and the trademark is in ownership system that is individual in the trademark and communal in GI.